Skrining Fitokimia Dan Uji Kadar Kurkumin Pada Fraksi Etil Asetat Rimpang Kunyit (Curcuma Longa) Dengan Metode Klt Dan Spektrofotometri Uv-Vis - Shary, Aprilya Kumala; Mahfur, Mahfur (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Turmeric (Curcuma longa) is a medicinal plant from the Zingiberaceae family which has the potential to be developed as a superior plant that has benefits and efficacy as a medicinal ingredient. Turmeric has a yellow dye called curcuminoids as much as 5% (50-60% curcumin, demethoxycurcumin and bisdemethoxycurcumin). The very basic content of turmeric is Curcuma or curcumin because it has the largest component. The purpose of this study was to determine the phytochemical content by conducting a screening test on the ethyl acetate fraction of turmeric rhizome using the TLC method and UV-Vis Spectrophotometry. This research method used descriptive method by means of observation or non-experimental. Phytochemical screening included tests for flavonoids, alkaloids, saponins, phenols, tannins and steroids/triterpenoids which carried out to determine the class of compounds contained in turmeric rhizome. The ethyl acetate fraction in turmeric rhizome suspected to contain curcumin, so a test for the levels of curcumin contained in turmeric rhizome was carried out. The results showed that the positive turmeric rhizome samples contained flavonoids, tannins, phenols and steroids. As well as negatively contain alkaloid compounds and saponins. The results of identification with TLC samples containing curcumin compounds according to the literature and the standard Rf value of curcumin is 0.75-0.80. The assay results using the UV-Vis Spectrophotometry method for the ethyl acetate fraction of turmeric rhizome samples yielded an average concentration of 159.79 mg⁄g.